Pre-historical language contact in Peruvian Amazonia a dynamic approach to Shawi (Kawapanan) - Rojas-Berscia, Luis Miguel 1991- (Contact language library, 2021)
"South America was populated relatively recently, probably around 15,000 years ago. Yet, instead of finding a relatively small number of language families, we find some 118 genealogical units. So far, the historical processes that underlie the current picture are not yet fully understood. This book represents a preliminary attempt at understanding the socio-historical dynamics behind language diversification in the region, focusing on the Kawapanan languages, particularly on Shawi. The book provides an introduction to the ideas behind the flux approach of Dynamic linguistics and later concentrates on prehistorical language contact, specifically in the northern Peruvian Andean sphere. The number of studies presented shed light on a layered picture in which a number of Kawapanan lects were used in non-polyglosic multilingual settings. The book explores the potential contact relationships between Kawapanan languages, Quechuan, Aymaran, Chachapuya, Cholón-Hibito, Arawak, Carib and Puelche. The analysis draws on data collected in the field over a period of eight years (2012-2020) with both Shawi and Shiwilu speakers and includes the first comprehensive grammar sketch of Shawi"